Pengendalian Gerak Longitudinal Pesawat Fixed Wing FT-Explorer - Enrico Hadi Pranata; Try Susanto; Rikendry Rikendry; Ajeng Savitri Puspaningrum (Universitas Teknokrat Indonesia, 2023)
Unmanned Aerial Vehicle (UAV) or often called an unmanned aircraft is a vehicle that can fly by being controlled using radio waves or flying autonomously. Unmanned aircraft have an electro-mechanical based system to be able to perform missions programmatically using the laws of aerodynamics. One of the unmanned aircraft is a fixed wing type aircraft, which has a control plane in the form of an aileron to control the roll angle, an elevator to control the pitch angle, and a ruder to control the yaw angle. When an aircraft goes on a flying mission, many disturbances are encountered that destabilize the flight of the aircraft, one of which is the weather. Weather can be in the form of strong winds that cause loss of stability and spinning and thwart the flight mission. Spinning is the state of the aircraft rotating on the longitudinal axis. Therefore, it is necessary to have a control system so that the aircraft can overcome these disturbances. One of the control methods that can be used is the PID control method. The PID control method utilizes Feedback error to reach the point of stability. The PID control method not only utilizes the current error, but previous errors and predicts future errors. Based on the test results, the PID control method applied to unmanned aircraft is able to overcome the given disturbance well. Evidently when tested by giving disturbance to the roll angle, the aircraft is able to overcome the disturbance and return to stable flight maintaining longitudinal motion. The best response results are obtained with an overshoot of 6.9o, rise time of 0.45 sec, settling time of 1.2 sec, and steady state error of 0.45o.